IMPLEMENTASI WEB FILTERING FIREWALL UNTUK KEAMANAN PADA JARINGAN INTERNET DI PONDOK PESANTREN AL HIDAYAH KEBUMEN - Ma'mun, Ahmad Sukron; Muflih, Ghufron Zaida (Universitas Budi Luhur, 2025)
In the digital era, unrestricted internet access can have both positive and negative impacts, particularly in educational settings such as Islamic boarding schools (pondok pesantren). This study aims to implement a web filtering firewall system based on Mikrotik RouterOS to enhance internet network security at Al Hidayah Islamic Boarding School in Kebumen. Utilizing the Mikrotik RB951Ui-2HnD device to manage network access and winbox for router configuration, this research applies a web proxy approach to restrict access to negative content such as pornography, online gambling, and online games, which may interfere with students' learning processes. The development process follows the Waterfall model, encompassing the stages of analysis, design, implementation, testing, and maintenance. Results from the implementation indicate that the system effectively blocks unwanted websites, thereby fostering a safer and more conducive internet environment for educational activities. This research can provide an effective solution in managing and controlling internet access at the Al Hidayah Islamic Boarding School, Kebumen.